Two new species of the genus Eubasilissa Martynov (Trichoptera: Phryganeidae) from the Indian Himalaya - Parey, Sajad H.; Saini, Malkiat S. (Zootaxa, 2012)
Two new species of the genus Eubasilissa Martynov are described and illustrated from the Indian Himalaya, namelyEubasilissa sikkimensis sp. nov. from Lachung (Sikkim) that appears close to Eubasilissa maclachlani (White, 1862) andEubasilissa schmidi sp. nov. from Bhaderwah (Jammu & Kashmir) that resembles Eubasilissa avalokhita Schmid, 1962.The female of Eubasilissa asiatica (Betten, 1909) is described and illustrated for the first time from Gurez valley (Jammu & Kashmir). With this addition of 2 new species, the genus Eubasilissa is now represented by 9 valid species from India.